Perancangan Sistem Penilaian Kinerja Perusahaan Berbasis Web Menggunakan Metode Balanced Scorecard (BSC) - Muhammad Alfarizi Harahap; Marina Elsera; Edrian Hadinata (LKP Unity Academy, 2023)
The balanced scorecard is a set of performance measures that cover four Kategori Produks, namely financial, customer, internal business processes and learning and growth. The word